REVISITING “GRAMMARLY” IN HIGHER EDUCATION (A LITERATURE REVIEW) - Vidya Arisandi,; Ajat Sudarajat, (Journal of Innovation Research and Knowledge, 2023)
The aim of this review is to analyze and synthesize existing literature on the effectiveness of Grammarly in improving undergraduate students' writing skills, which is crucial for their success in higher education. To achieve this, the writers conducted a search for ten relevant studies on Scopus and Science Direct journals. Through this evaluation, the study aims to shed light on the impact of Grammarly on the writing abilities of undergraduate students. Although Grammarly provides automatic feedback on sentence structure, its usefulness as a writing support tool for undergraduate students in higher education institutions is limited due to its restricted capacity to reformulate sentences, particularly when converting passive voice into active voice. The study suggests that future versions of Grammarly should incorporate advanced paraphrasing capabilities to enhance its effectiveness. This research highlights the significance of writing skills in higher education institutions and the advantages and limitations of artificial intelligence tools such as Grammarly.